A study of travel patterns in Surabaya metropolitan area - Abidin, Zainal Zulhilmi (Scopus Elsevier, 2020)
The Surabaya Metropolitan Area (SMA) in East Java Province is the second most important economic zone in Indonesia. It is composed of five Regencies, Sidoarjo, Mojokerto, Lamongan, Gresik, Bangkalan, and two Cities, Mojokerto, and Surabaya. There are not less than nine million people in the SMA region. The boundaries of the Surabaya Metropolitan Area are based on several factors namely the travel time and the distance from the center of Surabaya, the natural conditions and the urbanization patterns. The travel time to the city center of Surabaya is estimated to be 1 hour away with a distance of about 20 km. This condition has certainly changed since the operation of the Suramadu Bridge connecting the city of Surabaya and Bangkalan, therefore it will greatly affect the travel patterns of the population and the movement of people.